HUBUNGAN TINGKAT PENDIDIKAN BIDAN DENGAN TINGKAT PENGETAHUAN TENTANG STANDAR ANC PADA IBU HAMIL DI PUSKESMAS SUMBANG I DAN II KABUPATEN BANYUMAS TAHUN 2011 - Surtiningsih Surtiningsih; Stephani Aryana Heristawati (Universitas Harapan Bangsa Purwokerto, 2011)
Background of the research: Mother Death Rate (AKI) in Indonesia is still relatively high. Most of the death is caused by pregnancy and birth complication.One of the preventation is by raising the midwifery attendance that fill thestandard of safety and effectiveness.The standard used is ANC. Based on theformerly study in the Puskesmas Sumbang I and II, there are 17 DI midwife and15 DIII midwife, so that there is still variation in ANC Standard. Aim : To know the correlation between the Midwife Educational Gradewith the Knowledge Grade of the ANC Standard at the pregnancy mother inPuskesmas Sumbang I and II at Banyumas Regency in the 2011. Methode : Kind of research is Analitik Correlational by using the CrossSectional. The population of the research is all midwifes in Puskesmas I and II,they are all 32 midwifes with the Total Sampling. Kind of data is Primer with theQuestioner Instruments Result : There are 17 DI education grade midwifes (53.1%) and 15 DIIIeducation grade ones (46.9%). The midwifes with the good knowledge grade ofANC Standard are 18 person (56,2%) and the rest, with the average grade are 14person (43,8%). The result of the Rank spearman Correlation with the count-r is 0,828. Summary : There is a correlation between the midwife educational gradewith the knowledge grade of ANC standard in the pregnant mother at Puskesmas Sumbang I and II, at Banyumas Regency, in the 2011(p-value=0,000 <ï¡ = 0,05).Key Words : The midwife educational grade, the knowledge grade the grade knowledge of ANC Standard.